The effects of CMC on the mechanical properties of starch protein edible film: article - Razak, Nur Zufeeqah; Hamidon, Fariza (2017)
The purpose of this research is to investigate the effects of carboxymethyl cellulose (CMC) on the mechanical properties of starch protein edible film. Characterization such as tensile properties, water vapor permeability (WVP) and solubility in water were the focus of the investigation. It was found that CMC had significant effects on the tensile properties of the starch protein film. The addition of CMC to the starch protein films significantly increased elongation at break from 8.027 to 52.707% and tensile strength from 10.323 to 72.733 MPa. The incorporation of CMC in the films decreased the WVP significantly with 3.1939 x 10¯¹², 2.7025 x 10¯¹² and 2.2930 x 10-12 g.Pa¯¹h¯¹m¯¹ for films containing 0, 5, and 10% CMC respectively. However, when the CMC content of the films reached to 15%, the WVP increased significantly to 3.1529 x 10¯¹²g.Pa¯¹h¯¹m¯¹. The results of solubility in water showed that with the increase of CMC content in the starch protein film, the water solubility of films increased. The %TSM calculated were 45.23, 50, 62.96 and 71.01% for 0, 5, 10, 15% CMC, respectively. It was observed from this work that the content of CMC at 10% in the starch protein polymer matrix may be the best selection for desirable properties of edible film.